AB0159 Cytokine production by activated plasmacytoid dendritic cells and nk cells is suppressed by an irak4 inhibitor. (12th June 2018) - Hjorton, K.; Hagberg, N.; Israelsson, E.; Berggren, O.; Sandling, J.; Thorn, K.; Mo, J.; Eloranta, M.-L.; Rönnblom, L.
Abstract : Background: In SLE, immune complexes containing self-derived DNA or RNA (RNA-IC) trigger the synthesis of several pro-inflammatory cytokines by immune cells. Treatment with anti-malarials, such as hydroxychloroquine (HCQ), which through endosomal TLR inhibition effectively blocks IFN-α, is standard of care. However, few patients experience complete remission. Objectives: We asked how an IL-1 receptor associated kinase 4 (IRAK-4) inhibitor I92 (ND-2158, Nimbus Discovery), 1 acting downstream of TLR 7/9, affects RNA-IC-induced cytokine production compared to hydroxychloroquine (HCQ). Methods: Plasmacytoid dendritic cells (pDCs) and natural killer (NK) cells were isolated from peripheral blood mononuclear cells (PBMCs) of healthy individuals. PBMCs from 15 SLE patients were depleted of monocytes. Cells were stimulated with RNA-IC, consisting of IgG from SLE patient sera and U1snRNP particles, in the presence or absence of I92 or HCQ. Cytokines were measured by immunoassays or flow cytometry. RNA-sequencing was performed on RNA-IC stimulated pDCs from four healthy individuals and the effect of I92 and HCQ was assessed. Results: RNA-IC induced IFN-α, TNF-α, IL-6, IL-8, IFN-γ, MIP1-α and MIP1-β production in pDC and NK cell co-cultures. I92 reduced the pDC and NK cell derived cytokine production by 74.95%. HCQ interfered with cytokine production in pDCs, but not in NK cells. In monocyte-depleted SLE PBMCs I92 blocked TNF-α, IFN-γ, MIP1-α and MIP1-β production more efficiently than HCQ. IL-8 production was high in monocyte depleted PBMC from SLE patients, and not blocked by neither drug, despite significant inhibition of IL-8 in pDC-NK co-cultures from healthy individuals. Following RNA-IC activation of pDCs, 975 differentially expressed genes were observed (FDR<0.05), many connected to cytokine pathways, cell regulation and apoptosis. The IRAK4 inhibitor significantly changed more RNA-IC induced genes than HCQ (492 vs. 65 genes). Several top upregulated genes were reversed by both I92 and HCQ, including IFNA2, IFIT2-3, OASL, CXCL10, CD274, TNFSF10, APOL6 . Genes such as DKK4, LAD1 and EAF2 were significantly more downregulated by I92 than by HCQ. Conclusions: Whereas both HCQ and the IRAK4 inhibitor block important pro-inflammatory cytokines, the IRAK4i I92 exhibits a broader inhibitory effect than HCQ on pathways triggered by RNA-IC, which suggests that IRAK4 inhibition could be a future therapeutic option in SLE and possibly other systemic autoimmune diseases characterized by the presence of ICs containing nucleic acid. Reference: [1] Kelly PN, Romero DL, Yang Y, et al. Selective interleukin-1 receptor-associated kinase 4 inhibitors for the treatment of autoimmune disorders and lymphoid malignancy. J Exp Med 2015;212:2189–201. doi:10.1084/jem.20151074 Disclosure of Interest: K. Hjorton: None declared, N. Hagberg: None declared, E. Israelsson Employee of: AstraZeneca, O. Berggren: None declared, J. Sandling: None declared, K. Thorn Employee of: AstraZeneca, J. Mo Employee of: AstraZeneca, M.-L. Eloranta: None declared, L. Ronnblom: None declared